Multimedia Interaktif Pembelajaran Bahasa Arab Untuk Siswa Madrasah Aliyah - Yasmar, Renti (ARABIYATUNA : Jurnal Bahasa Arab, 2017)
This study aims to produce appropriate Arabic Learning Media for Madrasah Aliyah students viewed from the validation results of material experts, media experts and teacher and student responses to the developed Arabic Learning Interactive CD. This research is based on the lack of Arabic language learning media in Madrasah Aliyah Muhammadiyah Yogyakarta so that the teacher difficulties in dalm explain Arabic materials. This research type is research and development with stages consist of (1) needs analysis, (2) instructional design 3) product development, (4) Validation (5) Product assessment of teachers and students, (6) Final Product. The validation process is done by 1 media expert and 1 material expert. The subjects of the study were the teachers of Arabic Madrasah Muallimaat Muhammadiyah Yogyakarta at the level of Aliyah amounting to 2 people and the students of Madrasah Muallimaat Muhammadiyah Yogyakarta amounted to 30 students. The data were obtained using questionnaires for media experts and material experts as well as students responses or responses to media developed on the aspects of learning, material aspects, display aspects and programming aspects. Data were analyzed by quantitative descriptive analysis. The result of the research shows that the material expert judgment on the feasibility of Interactive CD of Arabic Learning from the learning aspect with the average 4,17 (good) and the material aspect with the average 4,00 (good). Assessment of media expert on the feasibility of Interactive CD of Arabic Learning from aspect of display with average 4,15 (good) and programming aspect with average 4,00 (good). Teachers responses to Interactive CDs Arabic learning shows that teachers give positive responses to Interactive CD of Arabic Learning seen from learning aspect with average 4,12 (good), material aspect with average 4,16 (good), aspect of display with average 4 , 19 (good), and programming aspect with average 4,21 (good). The result of responses or students responses to Interactive CDs The learning of Arabic shows that students give positive responses to Interactive CD of Arabic Learning seen from learning aspect with average 4,12 (good), material aspect with average of 4.10 (good), aspect of display average 4,07 (good), and programming aspect with a mean of 4.12 (good). The results of this study conclude that the Interactive CD of learning Arabic language developed feasible to be used for Madrasah Aliyah students